Purification, sequencing and structural characterization of the phospholipase A(1) from the venom of the social wasp Polybia paulista (Hymenoptera, Vespidae) - Santos, Lucilene D.; Santos, Keity S.; de Souza, Bibiana M.; Arcuri, Helen A.; Cunha-Neto, Edecio; Castro, Fabio Morato; Kalil, Jorge Elias; Palma, Mario Sergio [UNESP] (Elsevier B.V., 2007)
The biochemical and functional characterization of wasp venom toxins is an important prerequisite for the development of new tools both for the therapy of the toxic reactions due to envenomation caused by multiple stinging accidents and also for the diagnosis and therapy of allergic reactions caused by this type of venom. PLA(1) was purified from the venom of the neotropical social wasp Polybia paulista by using molecular exclusion and cation exchange chromatographies; its amino acid sequence was determined by using automated Edman degradation and compared to the sequences of other vespid venom PLA(1)'s. The enzyme exists as a 33,961.40 da protein, which was identified as a lipase of the GX class, liprotein lipase superfamily, pancreatic lipases (ab20.3) homologous family and RP2 sub-group of phospholipase. P. paulista PLA(1) is 53-82% identical to the phospholipases from wasp species from Northern Hemisphere. The use restrained-based modeling permitted to describe the 3-D structure of the enzyme, revealing that its molecule presents 23% alpha-helix, 28% beta-sheet and 49% coil. The protein structure has the alpha/beta fold common to many lipases; the core consists of a tightly packed beta-sheet constituted of six-stranded parallel and one anti-parallel beta-strand, surrounded by four alpha-helices. P. paulista PLA(1) exhibits direct hemolytic action against washed red blood cells with activity similar to the Cobra cardiotoxin from Naja naja atra. In addition to this, PLA(1) was immunoreactive to specific IgE from the sera of P. paulista-sensitive patients. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: wasp venom; phospholipase; immunoreactivity; IgE; molecular modeling; Hymenoptera; hemolysin; allergen